Recent advances in heavy metal/metalloid ion treatment from wastewater using nanocomposites and bionanocomposites - Singh, Namita; Yadav, Annu; Das, Sumistha; Debnath, Nitai (Frontiers in Nanotechnology, 2024)
To 04th Oct, 2023 The Editor, Fronteirs in nanotechnology-nanomaterials Dear Sir, We are submitting a review article entitled: "Recent advancements in nanocomposite and bionanocomposite mediated wastewater remediation with special emphasis on heavy metal removal" for your kind consideration. In this review article we have discussed the nanocomposite mediated wastewater decontamination strategies which mostly came up in recent years. Moreover, we have highlighted the potential of nanomatrix embedded bioaccumulating/biosorbing fungi as a new age wonder material with superior capability of pollutant removal from wastewater. We do hereby declare that the manuscript has not and will not be submitted for publication elsewhere so long as it is under consideration by "Fronteirs in Nanotechnology-Nanomaterials". We, Namita Singh, Annu Yadav, Sumistha Das, Nitai Debnath have participated in the study and concur with the submission and subsequent revisions submitted by the corresponding author.Yours sincerely, Prof.